COMPARATIVE STUDY OF ANTIOXIDANT AND ANTIMICROBIAL ACTIVITY OF ROOT, STEM AND LEAVES OF LEEA INDICA SPECIES - Harun, Aiza; Ab Rahim, Nor Erlena Asmira; Abd Jalil, Mohd Azfar; Muhammad Rosdi, Atiqah; Daud, Shaari; Suhaila Harith, Siti; Mat So’ad, Siti Zaiton; Mohd Hassan, Norazian (Malaysian Journal of Science, 2017)
In this paper, we investigate the potency of Leea indica locally known as Memali plant from Tasik Chini, Pahang as a potent antioxidant and antimicrobial agent. Antibacterial activity of root, stem and leaf extracts of L. indica was evaluated against skin disease caused-microb Staphylococcus aureus and Staphylococcus epidermidis. Antioxidant activity was assessed by 2,2 diphenyl-1-picrylhydrazyl ( DPPH) thin layer chromatography (TLC) and dot blot assay method. The dichloromethane (DCM) extracts of all three parts displayed obvious antibacterial effect compared to other extracts and DCM extracts from leaves was the most effective in inhibiting the growth of S. epidermis with inhibition zone (IZ) of 18 mm. The methanol extracts from stem scavenged DPPH radicals more effective than root and leaf extracts at a concentration as low as 0.19 mg/ml. The antibacterial and antioxidant properties of leaves and stem might be attributed to the high content of terpenoid and phenolic. Thus, Memali appears to be a promising source of bioactive ingredients with antioxidant and antimicrobial activity.